Book reviews - Laitila, Teuvo; Jouili, Jeanette; Wickström, Laura; Ahlbäck, Tore (Approaching Religion, 2011)
Four book reviews are included in this issue of Approaching Religion:The Process of Buddhist-Christian Dialogue (2009) by Paul O. Ingram is reviewed by Dr Teuvo Laitila. The book deals with contemporary dialogues between Buddhists and Christians, mainly in the West, by applying a three-part perspective denoted conceptual, engaged and internal.Producing Islamic Knowledge. Transmission and Dissemination in Western Europe (2010) by Martin van Bruinessen and Stefano Allievi is reviewed by Dr Jeanette Jouili. The book investigates into Islamic knowledge production taking place in the contemporary European context, from a theoretical as well as from a richly varied empirical perspective.Grounding Religion. A Field Guide to the Study of Religion and Ecology (2011) by Whitney A. Bauman, Richard R. Bohannon II and Kevin J. O’Brien is reviewed by MA Laura Wickström. The book provides an introduction to the field of religion and ecology with special emphasis on interreligious co-operation.Mirakel, mysterier och moraliteter. Från puritanism till New Age – en religionshistorisk studie av Helen Shucman och A Course in Miracles (2010) is reviewed by Dr Tore Ahlbäck. The book is a doctoral thesis analysing the history of creation behind the highly influential spiritual guide A Course in Miracles (1965–72) and its originator Helen Shucman.